A Cross-Sectional Study Between Organizational Commitment and Citizenship Behavior in Malaysian Bank Simpanan Nasional - Hemaloshinee, Vasudevan A. (International Islamic University, Malaysia, 2021)
This study aims at evaluating the relationship between organizational commitment on non-supervisory citizenship behavior in the Bank Simpanan Nasional, Malaysia. The focal point of the study is to find how negative individual points of view resulting in lack of commitment and the low degree of loyalty can impact employee manners such as insufficient professionalism, poor teamwork, less self-awareness and high turnover in the current situation. This undesirable trait was also found to be prevalent among other current banking industry situations. The survey and a systematic analysis method have been employed to achieve the research objectives. The sample numbered 172 (Male = 48.8%; Female = 51.2%) of the non-supervisory staff, selected through purposive or judgmental sampling. Respondents are selected among non-supervisory employees in this study. This study uses the quantitative method. The hypotheses further show a significant positive relationship between first order construct of organizational commitment and non-supervisory citizenship behaviorOrganizational and Individual. The relationship variables are examined using IBM Statistical Packages for the Social Sciences (SPSS) software Version 24. Findings of this study reveal that organizational commitment on citizenship behavior has a positive and significant relationship. This study recommends that the bank enhance employee commitment to promote positive citizenship behavior.